Applicability of an elastic band exercise program to wheelchair‐bound older adults with and without dementia: A self‐rating survey. Issue 2 (16th December 2018) - Hsiao, Chih‐Yin; Tsai, Athena Yijung; Chen, Kuei‐Min; Yao, Ching‐Teng
Abstract : Aim: To investigate the perceptions of wheelchair‐bound older adults with and without dementia toward the Wheelchair‐bound Senior Elastic Band exercise program, and to compare the differences of their perceptions to the program. Methods: A descriptive and comparative design was applied. Data were derived from the experimental groups of two cluster‐randomized controlled trials. A total of 133 participants from eight long‐term care facilities were recruited: dementia trial (four facilities, n = 73) and non‐dementia trial (four facilities, n = 60). All participants received the Wheelchair‐bound Senior Elastic Band exercises, which included three phases of warm‐up, aerobic motion and harmonic stretching, three times per week, 40 min per session for 6 months. The self‐rating survey using the criteria of simplicity, safety, appropriateness and helpfulness was applied to rate the program through face‐to‐face individual interviews at the end of the study. Results: Wheelchair‐bound older adults with or without dementia have positive perceptions of the Wheelchair‐bound Senior Elastic Band exercise program with regard to its simplicity, safety, appropriateness and helpfulness after 6 months of practice (mean scores ranged 8.75–9.59). No significant differences were found between groups on self‐rating of the program in most of the criteria. Conclusions: Older adults with dementia might be able to express their perceptions toward the exercise program through the self‐rating survey, as did the participants without dementia. The participants' perceptions provide direct feedback for modifying, improving and sustaining the long‐term implementation of the program.Geriatr Gerontol Int 2019; 19: 103–107 .